2021
DOI: 10.2147/rru.s317347
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics and Surgeon Comfort During Flexible Ureteroscopy

Abstract: The technological advancements of flexible ureteroscopy (FURS) and its accessories have resulted in broadening its indications to include the management of complex renal stones, with long operative time. The surgeon’s understanding about the ergonomics of the ureteroscopes and their cognizance of the operation theatre layout helps to improve their performance, including the surgical outcomes. This paper will describe the ergonomics that are involved in conducting FURS which in turn will aid in developing a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Recently, increasing attention in the field of human factors and ergonomics has been given to the theoretical models and practical meaning of comfort at work [1,2]. It has been observed that many ergonomic investigations have considered negative aspects of work, such as physical discomfort, illness, or musculoskeletal disorders [3].…”
Section: Introduction 1comfort At Workmentioning
confidence: 99%
“…Recently, increasing attention in the field of human factors and ergonomics has been given to the theoretical models and practical meaning of comfort at work [1,2]. It has been observed that many ergonomic investigations have considered negative aspects of work, such as physical discomfort, illness, or musculoskeletal disorders [3].…”
Section: Introduction 1comfort At Workmentioning
confidence: 99%
“…Second, this study did not analyze the ergonomic disparities between the two groups, which is one of the factors urologists take into account when selecting a surgical approach. 29 Thirdly, this study is a retrospective study conducted at a single center and includes a limited number of cases. Further investigation is necessary to validate the present findings by conducting prospective randomized trials and multicenter studies involving a larger patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the follow‐up period was short, possibly providing insufficient time to detect potential ureteral strictures using techniques such as NCCT. Second, this study did not analyze the ergonomic disparities between the two groups, which is one of the factors urologists take into account when selecting a surgical approach 29 . Thirdly, this study is a retrospective study conducted at a single center and includes a limited number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most studied ergonomic models is the surgeon performing laparoscopic surgery [31,32]. Current literature explores ergonomic concepts such as optimal bed height, monitor placement, adjustable screen heights, screen sizes, image quality and standing mat technology, which have been associated with improved provider comfort [33][34][35][36][37][38][39][40].…”
Section: Scope Of the Problemmentioning
confidence: 99%